Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikra Kecil dan Menengah (SAK EMKM) pada UD. Sumber Rejeki Bangsalsari - Yanti, Riska Linda; Nastiti, Ari Sita; F.A, Ibna Kamilia (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Indonesia is a developing country that cannot be separated from business activities carried out by both individuals and groups or commonly referred to as Micro, Small and Medium Enterprises. MSMEs have a very important role in creating jobs as well as helping the government in reducing the existing unemployment rate. As a business develops, it increases business funding. Banks/financial institutions will usually require financial reports to see the feasibility of granting credit. Financial reports function as a tool for analyzing financial performance which can provide information about financial position, performance and cash flow. Considering the important role of MSMEs in Indonesia, it is necessary to carry out records in accordance with Financial Accounting Standards (SAK). This standard has 3 components, namely the financial position report, profit/loss report and notes to financial reports which can assist in decision making. Keywords: MSME, financial reports, SAK EMKM.